Impacts of solar photovoltaic system on distribution network performance - Lau, Cheiw Yun (2017)
With the growth in energy demand and the depletion of fossil fuels, renewable energy resources have been seen as one of the most promising ways to sustain the future energy needs. However, the integration of renewables into the existing distribution networks can cause potential network problems. The issue is particularly acute if the renewable energy is generated from solar photovoltaic (PV) system with high variability. In this regard, this thesis deals with the modelling of a typical Malaysian distribution network that aims to analyze the impact of PV integration at distribution networks level. More specifically, the number of tap change for On- Load Tap Changer (OLTC) transformers is evaluated under various weather conditions; PV penetration levels as well as PV installed locations. The weather conditions were further categorized using variability index. In this way, the impact of solar variability can be properly assessed. The correlations of network losses and PV penetration levels have also been comprehensively analyzed. It is also important to highlight that actual solar PV generation data of various time resolution were collected and used in this work. This maintains the actual intermittency nature of PV generation. Furthermore, case studies have been performed for both low and medium voltage networks. The results suggest that sudden voltage variation and reverse power flow are the main concern of PV integration on the distribution network. The presented study shows that network losses are at the minimum level with a 50% PV penetration level. In addition, the findings suggest that high solar variability day could increase the tap change operations as much as 274% in average as compared to the network without PV system. In addition, a year-round analysis further suggests that the total annual tap change may operate 164% more frequently in average than a network without PV system.